Meta Analisis: Pengembangan Instrumen Tes Keterampilan Proses Sains dalam Pembelajaran Fisika dan IPA - Nafsih, Nurul Zakiatin; Festiyed, Festiyed; Mufit, Fatni (Universitas Negeri Padang, 2020)
21st century education requires that it produces quality human resources. The government is trying to answer the challenges of 21st century education through the development of the 2013 curriculum. In physics and science learning, discussing process skills Improve students' science learning process can be understood by updating. Real conditions in schools show that teachers have difficulty in talking. One solution is to develop an assessment instrument in the form of a test instrument for skills in learning physics and science. This study tries to analyze the value of validity, different power, level of difficulty, and reliability of the process skills test instrument. The research method used is meta-analysis. The sample used was 12 articles consisting of 10 national articles and 2 international articles. The research instrument used was an observation sheet complete with coding. The results were obtained for validity of 0, 75. The value of the difference in power was 0.30. Difficulty value is 0.45. The reliability value is 0.73. Can be refined tests developed can be used.